Incidence and Outcome of Late Relapse after Allogeneic Stem Cell Transplantation for Myelofibrosis - (:unkn) unknown (ELSEVIER SCIENCE INC, 2020)
In this cross-sectional study, we retrospectively evaluated the files of 227 patients with myelofibrosis who underwent transplantation between 1994 and 2015 for relapse later than 5 years after allogeneic stem cell transplantation (SCT). A total of 94 patients who were alive and in remission at 5 years were identified with follow-up of at least 5 years (median, 9.15 years) after SCT. Thirteen patients (14%) experienced late molecular (n = 6) or hematologic (n = 7) relapse at a median of 7.1 years while 81 patients did not experience relapse. Relapse patients received either donor lymphocyte infusion (DLI) (n = 7) and/or second transplantation (n = 4). Of those, 72.7% achieved again full donor cell chimerism and molecular remission, and after a median follow-up of 45 months, the 3-year overall survival rates for patients with or without relapse were 90.9% (95% confidence interval [CI], 77% to 100%) and 98.8% (95% CI, 96% to 100%), respectively (P = .13). We conclude that late relapse occurs in about 14% of the patients and the majority can be successfully salvaged with DLI and/or second allograft. All patients with molecular relapse are alive and support the long-time molecular monitoring in myelofibrosis patients after allogeneic SCT. (C) 2020 American Society for Transplantation and Cellular Therapy. Published by Elsevier Inc.
Keywords: Relapse; Allogeneic stem cell transplantation; Myelofibrosis; Donor lymphocyte infusion; DONOR-LYMPHOCYTE INFUSION; PROGNOSTIC SCORING SYSTEM; REMISSION; MUTATION; THERAPY; REGIMEN; IMPACT; BLOOD; PCR